2015
DOI: 10.1080/01904167.2015.1047522
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the photosystem II behavior of wild and cultivated barley in response to progressive water stress and rehydration using OJIP chlorophyll a fluorescence transient

Abstract: To study the effects of progressive drought stress on photosystem II behavior of wild (Spantaneum) and cultivated barley (Morocco), different levels of soil water availability, including control, moderate, mild, and severe water stress (70%, 50%, 30%, and 10% water holding capacity of soil, respectively) and rehydration were used. Polyphasic OJIP fluorescence transient of Morocco plants exhibited a considerable increase in fluorescence intensity at O, J, and I steps under mild and severe stress relative to sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…During winter and summer seasons, the upper and middle site showed more detectable increase in the J, I and P phases compared to the lower site could be derived from the significant reduction of moisture in the upper and the middle sites. Similar results were obtained by Ghotbi-Ravandi et al (2016) where moderate water loss (50% water holding capacity, WHC) did not show any considerable change with control condition (70% WHC), however, 30% WHC and 10% WHC showed significant difference in O-J-I-P steps. Higher fluorescent intensity was recorded in the winter season compared to the summer season in terms of lower, middle and upper sites which indicates more water stress in the grapevine in the winter season.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…During winter and summer seasons, the upper and middle site showed more detectable increase in the J, I and P phases compared to the lower site could be derived from the significant reduction of moisture in the upper and the middle sites. Similar results were obtained by Ghotbi-Ravandi et al (2016) where moderate water loss (50% water holding capacity, WHC) did not show any considerable change with control condition (70% WHC), however, 30% WHC and 10% WHC showed significant difference in O-J-I-P steps. Higher fluorescent intensity was recorded in the winter season compared to the summer season in terms of lower, middle and upper sites which indicates more water stress in the grapevine in the winter season.…”
Section: Discussionsupporting
confidence: 85%
“…The maximum quantum yield of primary photochemistry (F v /F m ) which is a reliable indicator of the physiological state of the plant against environmental stress ( Mehta, Allakhverdiev & Jajoo, 2010 ) was significantly decreased with decreasing moisture content in the soil. Under controlled conditions, F v /F m value is near 0.8–0.83 for most of the plants ( Björkman & Demmig, 1987 ; Ghotbi-Ravandi et al, 2016 ) which is equivalent to the photosynthetic rate of plants. In our study, in the winter season, F v /F m value for the lower, middle and upper sites was 0.80, 0.75 and 0.71, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors reported the use of the so-called L-and K-bands, calculated from the OJIP transient, which can be used as indicators of stress (Yusuf et al 2010, Redillas et al 2011, Paunov et al 2018. The JIP test analysis of the OJIP transient, developed by Strasser and Strasser (1995), is often used as a tool for detection and evaluation of plant tolerance to various abiotic stresses, e.g., salt stress (Zushi and Matsuzoe 2017), heat stress (Jedmowski and Brüggemann 2015), cold (Franić et al 2020), and drought stress (Dąbrowski et al 2019). Earlier studies have demonstrated that drought stress has negative effects on the efficiency of PSII, as indicated by changes in Chl fluorescence parameters, thus this method is useful for screening genotypes for the selection of droughttolerant cultivars (Guha et al 2013, Arslan et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Related researches showed that leaf metabolic disorder was caused by inhibition of electron transport through PSII during chilling stress (Bonnecarre `re et al 2011). OJIP transients indicate continuous reduction of electron transport in PSII and involves three distinct phases of fluorescence rise from O to P (Ghotbiravandi et al 2016). Recent studies on the freezing response of photosynthetic based on the OJIP test confirmed that OJIP used to predict plant chilling tolerance is reliable (Badeck and Rizza 2015;Rapacz et al 2015a, b).…”
Section: Discussionmentioning
confidence: 99%